How Self-Esteem and Sense of Belonging Drives Conspicuous Consumption - Alicia Listiani Tenia; Nabilah Putri Justine; Christian Haposan Pangaribuan (President University, 2022)
In order to prevent overconsumption, it is crucial to understand the causes of conspicuous consumption. The purpose of this study is to determine how self-esteem (SE) and a sense of belonging (SOB) relate to conspicuous consumption (CC). With an average age of early 20s in the Jakarta and Java region, 127 representatives of Generation Z are surveyed to collect data. Results revealed that both Self-Esteem and Sense of Belonging were strongly correlated with Conspicuous Consumption, according to correlation and regression analysis. We suggest for young adults to not purchase goods or items impulsively to avoid conspicuous consumption rather than displaying one’s wealth. Limitation and future research are discussed in context of the study’s findings.